Film blowing of PHBV blends and PHBV‐based multilayers for the production of biodegradable packages. Issue 2 (26th March 2015) - Cunha, Mara; Fernandes, Bruno; Covas, José A.; Vicente, António A.; Hilliou, Loïc; Lagarón, José M.; López‐Rubio, Amparo; Fabra, María José
ABSTRACT Poly(hydroxy butyrate‐co‐valerate) (PHBV) is a biodegradable polymer that is difficult to melt process into films. Such difficulty is mirrored in the lack of literature on film blowing of PHBV‐ or PHBV‐based materials. To circumvent this problem, 70/30 wt % blends of PHBV with a biodegradable compound (PBSebT), or with poly(butylene adipate‐co‐terephtalate) (PBAT), were prepared and tested for extrusion film blowing. Both blends showed a similar rheological pattern at 175°C, which is the maximum processing temperature with tolerable thermal degradation. Blending stabilized the film bubbles, thus widening the processing window. However, film properties such as tensile modulus, strain at break and tear resistance remained isotropic and crystallinity characteristics in the machine and transverse directions were generally similar. To bypass the thermal degradation associated with polymer blending, PHBV/PBAT films were coextruded. These showed enhanced functional properties when compared with films blown from blends. The mechanical properties of bilayered films matched those of films blown from commercial PBAT designed for food packaging. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42165.